Implementasi Nilai-nilai Pendidikan Muhammadiyah di Sekolah Dasar Muhammadiyah Alam Surya Mentari Surakarta 2015 - Raniyatushafa', Afif Arundina; Dr. Ari Anshori, M.Ag; Dr.Mutohharun Jinan, M.Ag (2016)
Education is a process of culture to increase human dignity through a long process and long life education. In the Islamic context, educational pattern desired by Islam is education that is capable of forming a superior human intellectually, rich in terms of charity, as well as graceful in policy and moral. Islam has the goal of education so that humans achieve personal balance as a whole. SD Muhammadiyah Alam Surya Mentari comes with the concept of nature-based early education. This concept is designed for individuals who give birth early mission of his creation as stewards and leaders on earth. The concept of early education program offers leadership and fun in learning. Each topic is discussed in a comprehensive lesson on the various dimensions of the appropriate level of student thinking. Students are invited to examine the growth of plants in the garden, looking at each occurrence and apply it in daily life. The research discusses the educational values of Muhammadiyah and aims to determine the implementation of the educational values of Muhammadiyah in the concept of nature in elementary school Muhammadiyah Surakarta Alam Surya Mentari, 2015. This research is a qualitative research. In assessing the problem, the researchers did not prove a hypothesis or theory that was made prior to the study. Researchers process data and analyze a non numeric problem, based on the flow theory about the qualitative research . This study focuses on the description of the data that have profound significance that comes from informants and observation of the behavior of research subjects. This research included in the category of field research (field research). The research approach used by researchers in examining this issue is an ethnographic approach to data collection techniques are observation, interviews and documentation. There are five points clear educational value of Muhammadiyah in SD Muhammadiyah Alam Surya Mentari that Islamic values, values of sincerity, tajdid value, the value of teamwork, and the value of caring. While the method of implementation of educational values in SD Muhammadiyah Alam Surya Mentari among them is the method of internalization, method of the story and method of habituation. The role of teachers in SD Muhammadiyah Alam Surya Mentari as a facilitator by using multi directional communication patterns that allow for equal opportunities for all learners and educators to interact.